2014
DOI: 10.3390/ijms151019074
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport Can Greatly Enhance Cdc20:Mad2 Formation

Abstract: To guarantee genomic integrity and viability, the cell must ensure proper distribution of the replicated chromosomes among the two daughter cells in mitosis. The mitotic spindle assembly checkpoint (SAC) is a central regulatory mechanism to achieve this goal. A dysfunction of this checkpoint may lead to aneuploidy and likely contributes to the development of cancer. Kinetochores of unattached or misaligned chromosomes are thought to generate a diffusible “wait-anaphase” signal, which is the basis for downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…They found that a diffusible signal can generally account for checkpoint operation. A more comprehensive model of the human SAC, including the Mad2 and BubR1 pathway, has been proposed by Ibrahim et al (2008a;2008b, 2009Ibrahim and Henze, 2014). A mathematical model for checkpoint activation based on the ''Mad2 template'' model by De Antoni et al (2005) is supported with in vitro experiments by Simonetta et al (2009).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…They found that a diffusible signal can generally account for checkpoint operation. A more comprehensive model of the human SAC, including the Mad2 and BubR1 pathway, has been proposed by Ibrahim et al (2008a;2008b, 2009Ibrahim and Henze, 2014). A mathematical model for checkpoint activation based on the ''Mad2 template'' model by De Antoni et al (2005) is supported with in vitro experiments by Simonetta et al (2009).…”
Section: Introductionmentioning
confidence: 78%
“…So far, mathematical models have helped to elucidate the kinetochore structure and with that the mitotic checkpoint mechanism (Doncic et al, 2005;Görlich et al, 2014;Ibrahim et al, 2007;2008b;Ibrahim and Henze, 2014;Kreyssig et al, 2012;Lohel et al, 2009;Sear and Howard, 2006;Simonetta et al, 2009;Tschernyschkow et al, 2013). However, none of these models consider the APC regulatory pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operator ∇ refers to the spatial gradient in spherical coordinates ( ∇(r, θ, ϕ) = ∂ ∂r e r + 1 r ∂ ∂θ e θ + 1 rsin(θ) ∂ ∂ϕ e ϕ ). Recent mathematical models of the SAC mechanism show that spherical symmetry can be used without loss of generality [27,20], and this form is used here. The system in Eq.…”
Section: Partial Differential Equations Modelmentioning
confidence: 99%
“…Also, the different components often interact nonlinearly in space and time, and in the presence of various feedback loops, which lead to remarkable phenomena that are difficult to predict [15,28,36,16,14,61]. Mathematical models have helped to illuminate fundamental modules of the SAC controls [8,53,21,40,20,22,27,45,37,25,13,24,26,29,3]. These models yet conceived SAC activation on details molecular level in order to distinguish between different pathways.…”
Section: Introductionmentioning
confidence: 99%